Observation of monoenergetic relativistic electron beams from intense laser - plasma interactions - Mangles, S; Murphy, C; Najmudin, Z; Thomas, A; Walton, B; Dangor, A; Krushelnick, K; Foster, P; Hooker, C; Langley, A; Collier, J; Norreys, P; et al. (Optical Society of America, 2006)
We report the observation of monoenergetic electron beams (dE/E < 5%) produced by the interaction of a 12TW, 40fs laser pulse with underdense plasma, in contrast to all previous experiments, which produced energy spreads ~100%. © 2005 Optical Society of America.